Dual-screw versus single-screw cephalomedullary nails for intertrochanteric femoral fractures: a systematic review and meta-analysis - Fan Yang; Xiafei Li; Lei Zhao; Qi Yang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Internal fixation with cephalomedullary nails has been widely used in the treatment of intertrochanteric femoral fractures (IFF). Yet, the difference in efficacy and safety between the commonly used integrated dual-screw cephalomedullary nail (InterTAN) and single-screw cephalomedullary nail remains inconclusive. Thus we performed the present systematic review and meta-analysis. Methods Randomized controlled trials (RCTs) or observational studies comparing InterTAN with proximal femoral nail anti-rotation (PFNA), the Asian PFNA (PFNA-II), or the Gamma3 nail in treating IFF were searched on PubMed, EMBASE, Web of Science and Cochrane Library from inception to April 30, 2023. The differences in perioperative parameters and clinical and radiological outcomes were evaluated by mean difference (MD) with 95% confidence interval (95%CI). The risks of various complications and mortality were assessed by risk ratio (RR) with 95%CI. Results Twenty-three studies comprising 3566 patients were included. Compared with single-screw cephalomedullary nails (PFNA/PFNA-II, Gamma3), InterTAN conferred significantly reduced risk of implant failures (RR = 0.37, 95%CI 0.26 to 0.51, P < 0.001), hip and thigh pain (RR = 0.70, 95%CI 0.55 to 0.90, P = 0.006) and all-cause revision/reoperation (RR = 0.38, 95%CI 0.26 to 0.57, P < 0.001). Moreover, patients treated with InterTAN had significantly higher 1-year Harris Hip Score (MD = 0.82, 95%CI 0.20–1.44, P = 0.010) and shorter time to union/healing (MD = − 0.66 days, 95%CI  − 1.16 to  − 0.16, P = 0.009). Femoral neck shortening, time to full bearing, and incidences of non-union, infection, deep venous thrombosis, and mortality were comparable between both groups. Conclusions The integrated dual-screw InterTAN construct has superior performance in reducing risks of complications and improving clinical and functional outcomes in the treatment of IFF. More well-designed, high-quality RCTs are warranted to confirm these findings.